Enhancing English Pronunciation Learning in Primary Education through Natural Language Processing: A Quantitative Study - Chandran, Mishalini; Wang, Shir Li; Dzulkifly, Sumayyah; Ng, Theam Foo; Ghoneim, Amr S. (Journal of ICT in Education, 2024)
Learning English pronunciation is crucial for primary school pupils to enhance their communication skills, yet many struggle. This study evaluates the effectiveness of a natural language processing (NLP) tool in improving English pronunciation among primary school pupils by measuring motivation, confidence, and performance. Conducted in a primary school in Johor, the research used a randomised controlled trial (RCT) design with 30 Year 3 pupils, divided into two groups of 15 each: control and treatment. The English teacher assessed motivation, confidence, and performance using a rubric-based evaluation, with a Cronbach’s Alpha value of 0.932, indicating high reliability. Paired t-tests were conducted to determine if the differences in motivation, confidence, and performance between the two groups were statistically significant. For motivation, t-values ranged from -1.871 to -1.468 for the traditional method and -6.548 to -13.229 for the NLP method. For confidence, t-values ranged from -1.871 to -1.468 for the traditional method and -11.500 to -7.135 for the NLP method. For performance, t-values ranged from -1.871 to -1.000 for the traditional method and -6.548 to -13.229 for the NLP method. With α = 0.05, the mean differences in motivation, confidence, and performance were significantly different for the NLP method (all p-values < 0.05) but not for the traditional method (all p-values > 0.05). High partial η² values, ranging from 0.474 to 0.827, suggest that the teaching methods account for a significant proportion of variance in the dependent variables. With α = 0.10, multivariate analysis of variance (MANOVA) assessed the effectiveness of the teaching methods. The combined dependent variables significantly differed based on teaching methods, Pillai Trace = 0.95, F(24, 5) = 3.72, p < 0.074, partial η² = 0.95. In conclusion, the study demonstrates that the NLP tool enhances English pronunciation learning by significantly improving motivation, confidence, and performance among Year 3 pupils.